Spatial Visualization of Human Anatomy through Art Using Technical Drawing Exercises. Issue 3 (3rd September 2021) - Na, Youjin; Clary, Derek W.; Rose‐Reneau, Zakary B.; Segars, Larry; Hanson, Andrea; Brauer, Philip; Wright, Barth W.; Keim, Sarah A.
Abstract : Spatial visualization, the ability to mentally rotate three‐dimensional (3D) images, plays a significant role in anatomy education. This study examines the impact of technical drawing exercises on the improvement of spatial visualization and anatomy education in a Neuroscience course. First‐year medical students ( n  = 84) were randomly allocated into a control group ( n  = 41) or art‐training group ( n  = 43). Variables including self‐reported artistic drawing ability, previous technical drawing experience, or previous anatomy laboratory exposure were gathered. Participants who self‐identified as artistic individuals were equally distributed between the two groups. Students in the art‐training group attended four 1‐hour sessions to solve technical drawing worksheets. All participants completed two Mental Rotations Tests (MRT), which were used to assess spatial visualization. Data were also collected from two neuroscience written examinations and an anatomical "tag test" practical examination. Participants in the art‐training and control groups improved on the MRT. The mean of written examination two was significantly higher ( P  = 0.007) in the art‐training group (12.95) than the control group (11.48), and higher ( P  = 0.027) in those without technical drawing experience (12.44) than those with (11.00). The mean of the anatomical practical was significantly higher ( P  = 0.010) in those without artistic ability (46.24) than those with (42.00). These results suggest that completing technical drawing worksheets may aid in solving anatomy‐based written examination questions on complex brain regions, but further research is needed to determine its implication on anatomy practical scores. These results propose a simple method of improving spatial visualization in anatomy education.